A standardized framework for quantitative assessment of cities' socioeconomic resilience and its improvement measures. (February 2022) - Kumar, Shantanu; Mehany, Mohammed S.Hashem M.
Abstract: Natural disasters, social unrest, and economic turmoil pose serious threats to major cities across the world. Socioeconomics is one of the drivers for disaster resilience since disaster events affect the social and economic growth of cities. Although many research studies addressed disaster preparedness, recovery, and other aspects of resilience, few have been dedicated to addressing socioeconomic resilience (SER) and even fewer addressed quantifying SER, presenting a problem that needs to be addressed. The objective of this research is focused on creating a standardized framework that quantifies and can compare, the SER of cities. The research efforts identify and establish the key performance indicators (KPI) through a content analysis followed by thematic analysis to create a final list of validated socioeconomic KPIs. The research results provide a threefold contribution to the research body of knowledge. Firstly, a standardized quantification mechanism, specific to the US, is created for assessing the SER of cities, which was further validated and piloted over three different cities as a case study. Secondly, the research introduces several improvement measures for each socioeconomic indicator which can help in restoring and improving these indicators and consequently the overall SER status. Finally, the research introduces an extensive list of different approaches for engaging and acquiring citizen buy-in to those improvement measures. The outcomes of this research can be used by city officials, policymakers, and community leaders among many other stakeholders to identify the weaknesses in their socioeconomic structure and implement measures to mitigate them. Highlights: Socioeconomic resilience and its quantification only sparingly addressed. Standardized socioeconomic framework for quantifying and comparing cities. Introduced improvement measures to enhance the socioeconomic resilience of cities. Citizen engagement approaches to acquire citizens' buy-in to the above measures. The framework will assist city officials, policymakers, and community leaders.